2020
DOI: 10.3390/ani10122350
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Based Gut Resistome Profiling of Broiler Chickens Infected with Multidrug-Resistant Escherichia coli

Abstract: The study was designed to investigate the fecal microbiome and resistome of broiler chickens infected with multidrug-resistant (MDR) Escherichia coli (E. coli). Fecal samples (n = 410) from broiler chickens were collected from thirteen randomly selected sites of Khyber Pakhtunkhwa and screened for the presence of MDR E. coli. Upon initial screening, thirteen (13) MDR E. coli isolates were then subjected to shotgun metagenome next-generation sequencing (NGS). NGS based resistome analysis identified the multidru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Arguably, a greater threat to human and animal health is posed by multidrug-resistant (MDR) bacteria, with an alarming increase being observed in the number of MDR strains isolated from the poultry meat production chain ( Afridi et al, 2020 ). Unusually high levels of MDR bacteria, especially those of the Enterobacteriaceae , have been isolated from poultry.…”
Section: The Use Of Antibiotics In the Poultry Industry And Its Effect On The Poultry Manure Resistomementioning
confidence: 99%
“…Arguably, a greater threat to human and animal health is posed by multidrug-resistant (MDR) bacteria, with an alarming increase being observed in the number of MDR strains isolated from the poultry meat production chain ( Afridi et al, 2020 ). Unusually high levels of MDR bacteria, especially those of the Enterobacteriaceae , have been isolated from poultry.…”
Section: The Use Of Antibiotics In the Poultry Industry And Its Effect On The Poultry Manure Resistomementioning
confidence: 99%
“…This change may be attributed to the detected significant increase in the transcript abundance of Escherichia ( Figure 7 ) after AGP + PFA administration at Day 35. In fact, in a previous study, the Escherichia genus was found to be the most common host for multidrug resistance ARGs ( Li B. et al, 2015 ; Xiong et al, 2018 ; Afridi et al, 2020 ). While interesting, we note that this may very well be also due to the fact that Escherichia coli is a popular model organism.…”
Section: Discussionmentioning
confidence: 95%
“…In chickens, Proteobacteria (38.9%) were dominant, followed by Firmicutes (36.4%), Bacteroidetes (15.8%), and Tenericutes (8.9%) (38). The differences between the abovementioned studies may be due to specific factors, such as animal species, growth stage, sampling position, and dietary components used.…”
Section: Discussionmentioning
confidence: 97%